Competencias en oftalmología. Aspectos a considerar en el desarrollo de competencias quirúrgicas en residentes de oftalmología (2013)
Teaching medicine involves a process of learning that allows for the development of specific competencies that will enable optimal performance for the future medical professional, the same applies to residents in surgical areas, who should also have special manual skills that will allow them to perform surgical procedures properly, but above all safety for the patient. After conducting a literature search about skills in medicine, followed by another about specific competencies in ophthalmology, a narration is made about the main definitions and academic approaches on the subject being developed by internationally renowned schools. In conclusion, the teaching and development of microsurgical skills in ophthalmology residents must have a sequence starting from simulated practice to get through to the real practice that allows for a safe and effective learning curve.